2005
DOI: 10.1007/s11199-005-4201-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Gender and Intimate Partner Violence from an International Perspective

Abstract: This paper reviews the international literature on intimate partner violence with a focus on gender differences in perpetration and victimization rates. A total of 35 studies from 21 countries are discussed that report prevalence or incidence rates of men's and women's involvement in physical and/or sexual aggression against an intimate partner. In addition, evidence on risk factors as well as consequences of intimate partner violence for men and women is presented. Conceptual and methodological differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 57 publications
(70 reference statements)
3
81
2
5
Order By: Relevance
“…Therefore, the idea can be urged that victims' require more contact with family or friends than they actually have -for instance because their violent partner forces them to remain silent -which in turn leads to more dissatisfaction about these contacts. Furthermore, concerning the role of gender and education level, inconsistent findings are reported in the overall literature (Krahé et al, 2005). This study showed that psychological violence affected all respondents, regardless of their age or education level.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…Therefore, the idea can be urged that victims' require more contact with family or friends than they actually have -for instance because their violent partner forces them to remain silent -which in turn leads to more dissatisfaction about these contacts. Furthermore, concerning the role of gender and education level, inconsistent findings are reported in the overall literature (Krahé et al, 2005). This study showed that psychological violence affected all respondents, regardless of their age or education level.…”
Section: Discussioncontrasting
confidence: 49%
“…Our Belgian findings are in line with the annual physical and sexual IPV prevalence rates of the Breiding et al (2008) the U.S. population-based survey, yet, they are lower than the general annual IPV prevalence estimates published in the review of Krahé and colleagues (2005), which rely on different sampling and survey methods. More specifically, Krahé et al (2005) included -next to representative samples -clinical and convenience samples which clearly lifted up the prevalence estimates whereas this study only reports on a representative sample, which have been found to detect lower estimates compared to other sorts of samples (Nielsen & Einarsen, 2008). Furthermore, except for the elevated levels of psychological IPV in the present study, our findings are in line with the French national representative survey (Jaspard et al, 2002) measuring IPV in an almost identical way as the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations